Styphlotrema solitaria Looss, 1899 (Digenea, Styphlotrematidae) infecting Eretmochelys imbricata Linnaeus 1758 (Testudines, Chelonidae) in Brazil - Werneck, Max Rondon; Silva, Reinaldo José da [UNESP] (My University, 2012)
The aim of the present study is to report the occurrence of Styphlotrema solitaria Looss, 1899 infecting sea turtles of the species Eretmochelys imbricata Linnaeus, 1758 found in the North Coast of São Paulo State, Brazil. Only nine S. solitaria specimens were found in the hosts studied, with a mean intensity of infection of 4.5. Since 2002, 14 specimens of E. imbricata from this region were necropsied and the prevalence of S. solitaria was 14.2%. New variations on morphological data were presented for this digenetic species. This is the first occurrence of S. solitaria in sea turtles from Brazilian Coast, expanding the information on the helminth fauna of E. imbricata and the geographical distribution of S. solitaria.

El objetivo de esta investigación es presentar la ocurrencia de Styphlotrema solitaria Looss, 1899 en las tortugas marinas de la especie Eretmochelys imbricata Linnaeus 1758 encontradas en el litoral Norte del Estado de São Paulo, Brasil. Apenas nueve especímenes fueron encontrados en los hospederos analizados correspondiendo a una intensidad media de 4,5. Desde el año de 2002, 14 ejemplares de E. imbricata provenientes de esta misma región fueron necropsiados lo que corresponde a una prevalencia de 14,2 %. Nuevas variaciones y datos morfológicos se presentan para esta especie de digeneo. Esta es la primera ocurrencia de S. solitaria en las tortugas marinas encontradas en el litoral brasileño, ampliando así la información sobre la helmintofauna de E. imbricata y distribución geográfica de S. solitaria.
Infección por Styphlotrema solitaria Looss, 1899 (Digenea, Styphlotrematidae) en Eretmochelys imbricata Linnaeus 1758 (Testudines, Chelonidae) en Brasil
Keywords: Brazil; Eretmochelys imbricata; Sea turtles; Styphlotrema solitaria; Trematoda; Brasil; Eretmochelys imbricata; Styphlotrema solitaria; Tortugas marinas; Trematoda